Advances in Mergers and Acquisitions, 8. - Finkelstein, Sydney (Emerald Group Pub., 2009)
What makes the Advances in Mergers and Acquisitions series stand out is its focus on all three characteristics that make up this research field studies from scholars in different countries, with different research questions, relying on different theoretical perspectives. Such a broad, and inclusive, approach to mergers and acquisitions is not easily replicated in academic journals, with much narrower mandates and metrics. The collections published each year provide cutting edge ideas by leading scholars on a global scale. Doing so not only broadens the questions being studied, but also helps.